The Relationship between Public Perception and the Role of Nurses in Health Services at the Public Poly of the Tapa Health Center, Bone Bolango Regency - Firawati Alinti; Herlina Jusuf; Yasir Mokodompis (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Public perception is an assessment, and public belief in the role of nurses in health services. The interaction between nurses and patients at the Public Poly of the Health Center is the main factor that shapes this perception. The attitude, communication, empathy, and professionalism of nurses in carrying out their roles as care givers, educators, communicators, and liaisons can affect the community's assessment of service quality. This study aims to determine the relationship between public perception and the role of nurses in health services at the Public Poly of the Tapa Health Center, Bone Bolango Regency. Types of quantitative research with survey methods. The research population is all patients who visited the Tapa Health Center General Polyclinic during the period of January 22-February 7, 2026. The total sample of 138 respondents was obtained using accidental sampling techniques. Data collection was conducted using public perception questionnaires and nurse role questionnaires. Data analysis using the Spearman Rank test. The results of the data analysis showed that there was a relationship between public perception and the role of nurses in health services at the Public Poly of the Tapa Health Center with a p-value of 0.000 (? 0.05) and a correlation coefficient value of 0.515 which showed a moderate strength of the relationship. In conclusion, there is a significant relationship between public perception and the role of nurses, where the better the role of nurses, the more positive the public's perception of nursing services. Suggestions to the Puskesmas and nurses can continue to improve the quality of nursing services so that public perception of services remains positive.